2024
DOI: 10.2147/ccid.s456470
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologists’ Knowledge, Attitude, and Practice Pattern Toward Low-Dose Oral Minoxidil in Hair Loss in Saudi Arabia

Saad Altalhab

Abstract: Background The utilization of low-dose oral minoxidil (LDOM) has emerged as a relatively new treatment option for hair loss, gaining recognition among dermatologists worldwide. Objective To assess the knowledge, attitude, and practice patterns among dermatologists in Saudi Arabia regarding the use of LDOM in the management of hair loss. Methods An online survey, which was distributed to dermatologists practicing in Saudi Arabia through email … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…With great pleasure, we have read the recent article written by Altalhab. We want to express our appreciation for the insightful study on “dermatologists’ knowledge, attitude, and practice pattern toward low-dose oral Minoxidil in hair loss in Saudi Arabia” 1 and provide our perspectives as medical students in the UK. Oral Minoxidil is an antihypertensive used for hair loss management, and this study showed that the usage of low-dose oral Minoxidil is increasing; however, many dermatologists may not prescribe this medication.…”
Section: Dear Editormentioning
confidence: 99%
See 3 more Smart Citations
“…With great pleasure, we have read the recent article written by Altalhab. We want to express our appreciation for the insightful study on “dermatologists’ knowledge, attitude, and practice pattern toward low-dose oral Minoxidil in hair loss in Saudi Arabia” 1 and provide our perspectives as medical students in the UK. Oral Minoxidil is an antihypertensive used for hair loss management, and this study showed that the usage of low-dose oral Minoxidil is increasing; however, many dermatologists may not prescribe this medication.…”
Section: Dear Editormentioning
confidence: 99%
“…Oral Minoxidil is an antihypertensive used for hair loss management, and this study showed that the usage of low-dose oral Minoxidil is increasing; however, many dermatologists may not prescribe this medication. 1 …”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations